Ultrasensitive Detection of Ochratoxin A With a Zeolite Imidazolate Frameworks Composite–Based Electrochemical Aptasensor - Ni, Xiao; Zhang, Yuyan; Xue, Chuhan; Chen, Xiaojun (Frontiers in Chemistry, 2022)
Ochratoxin A (OTA) is a harmful mycotoxin which is mainly secreted by Penicillium and Aspergillus species. In this work, an electrochemical aptasensor is presented for OTA detection based on Au nanoparticles (AuNPs) modified zeolite imidazolate frameworks (ZIFs) ZIF-8 platform and duplex-specific nuclease (DSN) triggered hybridization chain reaction (HCR) signal amplification. G-quadruplex-hemin assembled HCR nanowire acted as a nicotinamide adenine dinucleotide (NADH) oxidase and an HRP-mimicking DNAzyme. Besides, thionine (Thi) was enriched as a redox probe for signal amplification in this pseudobienzyme electrocatalytic system. Under the optimal conditions, the analytical response ranged from 1 to 107 fg·mL-1 with a detection limit of 0.247 fg·mL-1. Furthermore, the aptasensor was proven to be applied in real wheat samples with a recovery between 96.8% and 104.2%, illustrating the potential prospects in practical detection.